Math, asked by pipaltushar, 10 months ago

21x - 27y = 111; 27x - 21y = 129

Answers

Answered by AlluringNightingale
2

Answer :

x = 4 , y = -1

Solution :

Here ,

The given equations are ;

21x - 27y = 111 --------(1)

27x - 21y = 129 ---------(2)

Now ,

Adding eq-(1) and (2) , we have ;

=> 21x - 27y + 27x - 21y = 111 + 129

=> 48x - 48y = 240

=> 48(x - y) = 240

=> x - y = 240/48

=> x - y = 5 ----------(3)

Now ,

Subtracting eq-(1) from (2) , we have ;

=> (27x - 21y) - (21x - 27y) = 129 - 111

=> 27x - 21y - 21x + 27y = 18

=> 6x + 6y = 18

=> 6(x + y) = 18

=> x + y = 18/6

=> x + y = 3 ----------(4)

Now ,

Adding eq-(3) and (4) , we have ;

=> x - y + x + y = 5 + 3

=> 2x = 8

=> x = 8/2

=> x = 4

Now ,

Putting x = 4 in eq-(4) , we have ;

=> x + y = 3

=> 4 + y = 3

=> y = 3 - 4

=> y = -1

Hence ; x = 4 , y = -1 .

Answered by MinersCurse
0

Answer:x = 4 , y = -1

Step-by-step explanation:

Here ,The given equations are ;

21x - 27y = 111 --------(1)

27x - 21y = 129 ---------(2)

Now ,

Adding eq-(1) and (2) , we have ;

=> 21x - 27y + 27x - 21y = 111 + 129

=> 48x - 48y = 240

=> 48(x - y) = 240

=> x - y = 240/48

=> x - y = 5 ----------(3)

Now ,

Subtracting eq-(1) from (2) , we have ;

=> (27x - 21y) - (21x - 27y) = 129 - 111

=> 27x - 21y - 21x + 27y = 18

=> 6x + 6y = 18

=> 6(x + y) = 18

=> x + y = 18/6

=> x + y = 3 ----------(4)

Now ,

Adding eq-(3) and (4) , we have ;

=> x - y + x + y = 5 + 3

=> 2x = 8

=> x = 8/2

=> x = 4

Now ,

Putting x = 4 in eq-(4) , we have ;

=> x + y = 3

=> 4 + y = 3

=> y = 3 - 4

=> y = -1

Similar questions